Heritage and adaptation: Greek Australian musicians in Melbourne. Issue 2 (1st August 2019) - Southcott, Jane; Georgoulas, Renee
This study explores music-making by three bilingual bicultural Greek Australian musicians in Melbourne, Victoria. The formation and development of hybridized musical identity is a complex process for those who straddle two cultures. Our participants are musicians who work together as community, in the community and for the community. Data were gathered by semi-structured interviews and analysed using interpretative phenomenological analysis. The three Greek Australian participants in this study represent a continuum that encompasses the maintenance of tradition per se, with a focus on heritage preservation, and the blending and cross fertilization of traditions both Greek and non-Greek. This research illustrates how Australia's complex and diverse bicultural and multicultural musical identities are becoming the norm. Understanding the diverse musical identities of Australians with hybrid identities not only offers insight into how individuals construct their identity but also reveals how society embraces difference and cultural complexity. Such understanding can assist educators and community musicians facilitate effective music-making, teaching and learning.